2021
DOI: 10.1177/03000605211061029
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for ventilator-associated pneumonia in trauma patients with torso injury: a retrospective single-center study

Abstract: Objective We aimed to identify the risk factors for ventilator-associated pneumonia in patients admitted to critical care after a torso injury. Methods We retrospectively evaluated 178 patients with torso injury aged >15 years who were intubated in the emergency room and placed on a mechanical ventilator after intensive care unit (ICU) admission, survived for >48 hours, had thoracic and/or abdominal injuries, and had no end-stage renal disease. We compared clinico-laboratory variables between ventilator-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…The authors hypothesized that the two mechanisms by which hydrogen exerts its anti-inflammatory effects are activation of the anti-apoptotic system through the inhibition of ROS activity and direct modulation of inflammation through regulatory T cells (Tregs) involved in the regulation of autoimmunity and suppression. [38] NLRP3 inflammasomes are also an important pathway for the regulation of apoptosis in organisms, and the results of our study are consistent with this hypothesis. However, the exact mechanism underlying the anti-inflammatory effect of H 2 remains unclear, and more in-depth mechanistic studies are needed in the future.…”
Section: Discussionsupporting
confidence: 90%
“…The authors hypothesized that the two mechanisms by which hydrogen exerts its anti-inflammatory effects are activation of the anti-apoptotic system through the inhibition of ROS activity and direct modulation of inflammation through regulatory T cells (Tregs) involved in the regulation of autoimmunity and suppression. [38] NLRP3 inflammasomes are also an important pathway for the regulation of apoptosis in organisms, and the results of our study are consistent with this hypothesis. However, the exact mechanism underlying the anti-inflammatory effect of H 2 remains unclear, and more in-depth mechanistic studies are needed in the future.…”
Section: Discussionsupporting
confidence: 90%
“…Compared to patients who did not have hospital-acquired pneumonia, those with hospital-acquired pneumonia had worse outcomes and experienced elevated intracranial pressure ( 4 ). There was a significant association between ventilator-associated pneumonia, prolonged ICU stays, and mechanical ventilation durations ( 22 ). A prospective observational study by Chiara Robba et al included TBI ICU patients from multi centers in Europe and found an association between an increased risk of VAP and a high risk for respiratory failure in the ICU.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors include age, younger alcohol abuse, drug abuse, thoracic trauma, chest trauma, histamine-receptor antagonist intake, and antibiotic prophylaxis ( 23 ). Compared to non-trauma patients, intubated patients in ICU with trauma had a four times higher VAP incidence rate ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Xu et al [12] also indicated the following risk factors: the number of central venous catheters, the duration of maintaining the catheter in the urinary bladder, the number of antibiotics administered, and the use of corticosteroids before mechanical ventilation. In the research conducted by Lee et al [13], VAP was strongly correlated with the severity of an injury, the use of vasopressors and the insertion of a nasogastric tube.…”
Section: Introductionmentioning
confidence: 97%